Interfacing TRNSYS with MATLAB for Building Energy System Optimization - Josef Meiers; Georg Frey (Energies)
This contribution investigates whether the use of the MATLAB Optimization Toolbox on a parameter identification problem for a TRNSYS model provides better performance in iteration time. It presents the development of a framework connecting the MATLAB Optimization Toolbox with TRNSYS on the one hand and coordinating the optimization process of a TRNSYS model by GenOpt through MATLAB on the other hand. A benchmark framework in MATLAB was created to link TRNSYS and MATLAB and to configure the optimization process of GenOpt and the MATLAB Optimization Toolbox. Using this framework, a comprehensive comparison of the optimization solvers in GenOpt and the MATLAB Optimization Toolbox for the identification of the overall heat transfer coefficient of a TRNSYS heat exchanger model regarding the optimization time and number of iterations is presented as a use case. The results for the given problem show that GenOpt gives slightly better results in optimization time, whereas MATLAB has more potential and flexibility.